THE LEGAL IMPLICATIONS OF QARDH FINANCING FOR STAKEHOLDER WELFARE IN ISLAMIC ECONOMIC LAW - Saifuddin Zuhri (JURNAL HAKAM, 2026)
In the context of Baitul Maal Wa Al Tamwil (BMT) Maslahah, qardh loans are a financial product that, according to Sharia principles, do not require material compensation. Qardh loans are a product aimed at wel fare by assisting members with capital, facilitating qardh loans, and building relationships of trust and solidarity among members. The nadzar (vow) in qardh loans involves members providing alms to the BMT for the benefit of stakeholders. This research focuses on the integration of nadzar (vow) into qardh loans, which has implications for stakeholder welfare and BMT profits, a theory lacking in Islamic economics. The method used in this research is qualitative, using a case study approach at BMT Maslahah in East Java. The results indicate that qardh loans have implications for stakeholder welfare. Borrowing members enjoy ease of application requirements and relatively quick disbursement, principal repayment as agreed, interest-free installment payments, low administrative fees, and no collateral. Qardh loans are accompanied by a nadzar (vow) contract, where members provide alms to the BMT for income. BMT income is accumulated with other financing income for BMT operations and monthly remaining operating results (SHU) which are distributed to members in the form of bonuses and profit sharing of savings deposits. Meanwhile, the annual remaining operating results (SHU) are distributed to stakeholders, namely BMT reserve funds of 20%, management fees of 5%, management fees of 10%, member education funds of 5%, social funds of 10% and members receive 50% according to the portion of capital each year. So it is known that 85% of members stated that it has increased their income and improved their welfare and 15% of members stated that it has facilitated loan installment payments.